POLA ASUH ANAK DI TEMPAT PENITIPAN ANAK (STUDI KASUS DI PERUSAHAAN PT.TPP KECAMATAN LIRIK) - Sudarningsih "; M. Razif " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Parenting to children is how caregivers or parents in raising children, whose main purpose is caring for children and educate them properly though with various cara.Pola parenting is one critically important factor in developing or inhibiting the growth of creativity. The purpose of this study was to determine the pattern of care is done in Daycare and causes parents entrust their children in child care place. Data collection methods used are field research and literature study with qualitative data analysis descriptive that is by making a description of several phenomena found in the field. As for how parenting is conducted in this study is that authoritarian parenting (coercion), democratic (invited), and permissive (indifferent). The factors that cause children entrusted in Daycare This is because of busy parents, especially mothers who work outside the home to meet the needs of the economy. Parenting is used in Daycare is a democratic parenting style that is taking children but do not force him. Keywords: parenting, authoritarian, democratic, permissive, factors that influence